Improving Rabbiteye Blueberry Performance in a Calcareous Soil by Growing Plants in Pits Filled with Low-CaCO3 Growth Media - Guy Tamir; Dagan Eli; Shmuel Zilkah; Asher Bar-Tal; Nir Dai (Agronomy, 2022)
Calcareous soils are not suitable for blueberry cultivation. Our aim was to improve the performance of blueberry plants in calcareous soils by using pits filled with growth media in combination with high levels of RNH4+ (proportion of N-NH4+ among the total applied N). Rabbiteye blueberry (Vaccinium virgatum Ait. cv. Ochlockonee) plants were grown in pits filled with a tuff/peat mixture (TP), a sandy soil (S) or a calcareous (CC), in full factorial combination with three levels of RNH4+: 33%, 66% or 100%. The two higher RNH4+ treatments decreased the pH of the low-CaCO3 (S) and no-CaCO3 (TP) media to ≤6.0 over 250 days of fertilization, but did not affect the pH of the CC soil over 650 days. Plant performance was superior in the TP and S media, as compared to the CC soil. The type of growth medium was the dominant factor accounting for the improved plant performance. The plants were sensitive to Mn deficiency in leaves during the spring period. The current results suggest that growing blueberry in pits filled with good aeration and low pH buffering capacity medium in combination with a high level of RNH4+ is a positive approach for its cultivation in calcareous soils.